Analisis Implementasi Strategi Pemasaran Agen dalam Meningkatkan Penjualan Polis Asuransi Jiwa Syariah pada AJS Bumiputera Cabang Medan - Devi Ramadhani; Rahmi Syahriza (Universitas Muhammadiyah Surabaya, 2022)
AbstrackInsurancei is a companyi that hasi growni rapidly, each company also has a marketing strategyi ini offeringi products that exist in the company. The purpose of this study was to determine the agent's marketing strategy in increasing sales of sharia life insurance policies at AJS Bumiputera Medan Branch. This research uses qualitative research. Data collection techniques are carried out by conducting field research: observation, interviews and documentation. The results of the analysis of the implementation of agent marketing strategies in increasing sales of sharia life insurance policies at AJS Bumiputera Medan Branch are the agency system has a very large marketing system. Sales success is highly dependent on the performance of agents because it is from agents that in general sharia insurance products can reach prospective policyholders. In marketing this agent must also provide services in increasing sales of the Life Insurance policy where customers are satisfied with the services provided by the agent because the service provided is very good, and in increasing sales of this policy, it also gains market share, as well as profits, and also has good customer equity. Keywords: Marketing Strategy, Agent, Sales of Life Insurance Policies